Semen Characteristics and Superoxide Dismutase and Malondialdehyde Levels in Peshmerga Forces Exposed to Chemical Weapons during the ISIS-Related War - Yasin Kareem Amin (Cutting Edge Research in Biology Vol. 3, 2023)
The identification of chemical weapons as “weapons of mass destruction” highlights their possible damaging consequences on many civilians’ health. The effect of chemical weapon agents has been documented to cause reproductive toxicity and have adverse effects on semen, leading to infertility in those exposed to those chemical agents. This study analyses the semen fluid and follows up the exposed Peshmerga forces to the chemical weapon during the ISIS war. A prospective cohort study in which 58 exposed Peshmerga in three chemical attacks, compared with the same number of the non-exposed Peshmerga. Semen fluid analysis was performed for all, following up after one year. The serum level of both MDA and SOD was measured. An individual’s BMI was calculated. The participants’ mean age in this study is (32.5) years in the case group while (35.5) years in the control group, with a standard deviation of 5 years in both groups. All participants are male, and no gender effect be seen. All chronic illnesses have been excluded from the study. The mean body mass index is 22.4, with a standard deviation of about 3.1 kg/m. Hypospermia developed in 18% of the exposed group (20% of the total participants), oligospermia (20% overall, only 3% of these in the non-exposed), and decreased motility in 19% of all participants, but 16 of this 19% where the exposed group with significant relative risk results, while morphology not changed in both groups, also the findings showed that significant elevation in MDA level and SOD activity. Chemical weapons can significantly affect semen fluid analysis and interpretation through quantitative disturbances in the volume and account of sperm, while the percentage of abnormal sperm counts has been increased considerably in peoples exposed to chemical weapons. However, the morphology of semen fluid sperms has not changed to the same degree, and it’s function cannot be estimated. Even when functioning, the genetic errors on future generations may need further testing.